Effect of short term external perturbations on bacterial ecology and activities in a partial nitritation and anammox reactor. (November 2016) - Wu, Sha; Bhattacharjee, Ananda S.; Weissbrodt, David G.; Morgenroth, Eberhard; Goel, Ramesh
Graphical abstract: Highlights: Low temperature and sulfide in the wastewater adversely affected PN/A reactor performance. Ammonium oxidizing bacteria has more resilience than anammox bacteria to stresses. AOB activity was inversely correlated with amoA gene expression. hzsA gene expression was positively correlated with the activity of AMX. The role of flanking populations, such as members of the phylum Chloroflexi, in PN/A systems needs further investigation. Abstract: This research investigated the short term effects of temperature changes (lasting 2–4 weeks each) from 35 ± 2 °C to 21 ± 2 °C and 13 ± 2 °C and sulfide toxicity on partial nitrification-anammox (PN/A) system. Temperatures below 20 °C and sulfide content as low as 5 mgS  L −1 affected both aerobic and anaerobic catabolic activities of ammonia oxidation and the expression of related functional gene markers. The activity of AOB was inversely correlated with ammonium monooxygenase ( amoA) gene expression. In contrast, the activity of AMX bacteria was positively correlated with the expression of their hydrazine synthase ( hzsA ) gene. Although the overall activities of AMX bacteria decreased at lower temperatures, the AMX bacteria were still active at the low temperatures. The inverse correlation between amoA gene expressions and the corresponding AOB activities was surprising. 16S rDNA based high throughput amplicon sequencing revealed the dominance of Chloroflexi, Planctomycetes and Proteobacteria phyla the distribution of which changed with temperature changes.